Family Empowerment in Increasing Self-Efficacy and Self-Care Activity of Family and Patients with Pulmonary Tb - Muhtar Muhtar (Universitas Airlangga, 2013)
Introduction: Self-management and follow-up care at home is the key to a comprehensive pulmonary Tb management. One way to increase patient’s self-effi cacy and self-care activity is family empowerment. This study was aimed to prove the in fl uence of family empowermant in increasing self-effi cacy and self-care activity family and Pulmonary Tb patients.Method: This research used quasy experiment with non-randomized control group pre-posttest design. Population was family who lived with Pulmonary Tb patient, listed at Puskesmas Paruga and Mpunda. Samples were 32 respondents, divided into treatment and control group. Data were collected using questionnaire. Data were analyzed by using Wilcoxon Sign Rank Test, Mann-Whitney test, and Spearman Rho with level of signi fi cance 5%.Result: The results of Wilcoxon Signed Rank Test and Mann-Whitney Test showed value of p < 0.05. It means family empowerment had in fluenced on patient’s self effi cacy (p = 0.001), self-care activity (p = 0.001), family’s self effi cacy and self care activity (p = 0.002), and family’s role (p = 0.001). While, Spearman’s rho analysis revealed p = 0.001, which means self-effi cacy has signi fi cant relationship with self-care acitivity.Discussion: Family empowerment affects family knowledge and action in the treatment of pulmonary Tb patients. Family have an important role to improve patient’s self-effi cacy and self-care activity. Further research should develop nursing interventions, which useful for the improvement of self-effi cacy, self-care, medication adherence, and quality of life patients with pulmonary Tb.